2007
DOI: 10.1089/end.2006.0238
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cystolithotomy of Large Urinary-Diversion Calculi Using a Combination of Laparoscopic And Endourologic Techniques

Abstract: Our technique of percutaneous cystolithotomy utilizing laparoscopic and endourologic instrumentation is safe and effective for the removal of large calculi from urinary diversions. It is well tolerated, allows complete stone removal in a single sitting, and obviates an open procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…It is reported that the prevalence of urolithiasis has been markedly increasing, in parallel to the environmental factors such as dietary habits and lifestyle which reflect the rising in living standard [2]. The stone composition also has changed during the period [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the prevalence of urolithiasis has been markedly increasing, in parallel to the environmental factors such as dietary habits and lifestyle which reflect the rising in living standard [2]. The stone composition also has changed during the period [3].…”
Section: Discussionmentioning
confidence: 99%
“…Both transurethral and percutaneous approaches have been proved efficient for bladder stone management (16)(17)(18). Miller et al tested stone extraction by percutaneous CYS using the EndoBag Entrapment sac (US Surgical, Norwalk, CT) in a prospective study comprising patients with augmented bladders (17).…”
Section: Discussionmentioning
confidence: 99%
“…The entrap- ment sac perforated in 1 of 4 cases due to disproportional sac and stone dimensions, which led the authors not to recommend its use when adjuvant lithotripsy is required. Lam et al tested the same device and used ultrasonic lithotripsy in 8 patients with large calculi (mean size of 41 mm) (18). All patients were rendered stone free after a single procedure and the device was considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…2). Two large stones were put inside the laparoscopic entrapment sac that was inserted through the first trocar port site [1,4]. The stones inside the laparoscopic entrapment sac were fragmented by a lithoclast.…”
Section: Case Reportmentioning
confidence: 99%